Learning Design: Integration of Problem Posing and Problem Solving on Students' Mathematical Creativity in the SPLSV Material - Riski Anan Tama; Atmini Dhoruri (Eduvest - Journal of Universal Studies, 2026)
This research aims to develop an innovative learning design that integrates problem solving and problem posing approaches to students' mathematical creativity. The research method used is 'Analysis, Design, and Develop' (ADD), Analysis includes problem identification, theory studies, and determination of creative thinking indicators, namely fluency, flexibility, originality, and elaboration. Design formulates measurable learning objectives, while the development stage produces a learning design based on the integration of problem solving and problem posing. The results of the research are in the form of a learning design which is prepared in several stages, namely (1) orientation, which introduces the basic concept of SPLSV and the importance of problem solving and problem posing approaches; (2) problem solving, which includes understanding the problem, planning the solution, implementing the solution, and re-examining the solution; (3) problem posing, which involves students in designing new problems, solving them, and developing or modifying problems to make them more challenging; and (4) reflection, where students evaluate learning and identify the indicators of creativity that have been developed. The conclusion of this study is that a learning design that integrates problem solving and problem posing is expected to provide a relevant, innovative learning experience, and improve students' creative thinking skills in mathematics learning. This design has the potential to be a practical guide for teachers and a contribution to the development of a curriculum that emphasizes mathematical creativity.